SEARCHING FOR TASKS: TASK-ORIENTATION AND THE PROCESSUALITY OF DIGITAL SKILLS - Stewart, Nicole; Lesage, Frederik (AoIR Selected Papers of Internet Research, 2020)
Skills are not “out there” to be learned but develop through their enactment in situ. Rather than defining skills using a tool- or media-driven approach, we understand skills as situated, embodied processes known as ‘task-orientation’. Coined by Tim Ingold (2011, p. 195) this term refers to “any practical operation, carried out by a skilled agent in an environment as part of his or her normal business of life”. Part of this approach entails taking a holistic, narrative approach to investigating everyday life (Ingold, 2000; 2006; 2011) which some scholars have applied to digital media use (Moores 2017; Sumartojo et al. 2016; Pink 2016, 2015; Pink & Leder Mackley 2013; Pink 2011). We believe task-orientation offers a flexible way to define tasks performed online and offline encompassing three interrelated themes: 1) the processional quality of tool use; 2) the synergy of practitioner, tool, and material; and, 3) the coupling of perception and action. Our focus for this project is an investigation into how people perform unfamiliar tasks with digital media using the four processional phases. Unfamiliar tasks are an inherent part of our digitally-mediated everyday life to the extent that we have learned to ‘cope’ (see Sigaut 1994; see Ingold, 2000, p. 332; see also Nicolosi & Falsaperna, 2015, p. 71) with them — making them, in turn, one of our most ubiquitous and essential digital skills.